RESTITUTION THROUGH AUDIO-VISUAL MEDIA IN SPIRITUAL GROWTH OF SUNDAY SCHOOL CHILDREN - YOYOK FEBRIJANTO (Pedagogic Research-Applied Literacy Journal, 2024)
The modern technology made children less interested in going to Sunday School, they preferred to stay at home watching various interesting shows on their handphones. Another fact, the teaching model in Sunday School was monotonous and seemed traditional ways, so Sunday School teachers were required to be more creative and innovative in their teaching. One way was using audio-visual media through restitution patterns for children. This research’s purpose was to overview the importance of restitution through audio-visual media in the spiritual growth of Sunday School children. This research used a descriptive qualitative research method using a literature study approach. The research results showed that in restitution process, collaboration between teachers and children through audio-visual media played important role in the spiritual growth of Sunday School children such as increasing children's interest in learning the truth of God's Word, helping children remember the material presented by Sunday School teachers, motivating children to be diligent in Sunday School worship.